Sharia Insurance Perspective On Accident Insurance Claim Service Mechanism (Case Study atAPT. SunALifeAFinancial Unit Syariah Medan City Branch) - Amelia Putri Nasution; Rahmi Syahriza (Penerbit Jurnal Indonesia, 2022)
When a disaster occurs to the insured, such as an accident, the insured or the customer will submit a claim, so there are often misunderstandingsAbetween the insuredAand the insurer. Such as theAprocedures andAconditions thatAmust be met by the insuredAand the complicatedAclaim submission process. This is what makes the assessment of insurance worse in the eyes of the public. This study aims to discuss the Sharia Insurance Perspective on the Accident Insurance Claim Service Mechanism (a case study at PT. Sun Life Finansial Sharia Unit MedanABranch). TheApurpose ofAthisAresearchAis to find out howAthe mechanismAof accidentAinsuranceAclaim serviceAat PT Sun LifeAFinansial Syariah UnitAMedan Branch is in accordance with sharia insurance principles or not. ThisAresearch isAa qualitativeAresearch. TheAmethod of collectingAdata was throughAtwo stages, namelyAinterviews, and observations. The results of the study indicate that